Lactobacillus and Pediococcus ameliorate progression of non-alcoholic fatty liver disease through modulation of the gut microbiome. (3rd July 2020) - Lee, Na Young; Yoon, Sang Jun; Han, Dae Hee; Gupta, Haripriya; Youn, Gi Soo; Shin, Min Jea; Ham, Young Lim; Kwak, Min Jung; Kim, Byung Yong; Yu, Jeong Seok; Lee, Do Yup; Park, Tae-Sik; et al.
ABSTRACT: Targeting the gut-liver axis by modulating the gut-microbiome can be a promising therapeutic approach in nonalcoholic fatty liver disease (NAFLD). The aim of this study was to evaluate the effects of single species and a combination of Lactobacillus and Pediococcus in NAFLD mice model. Six-week male C57BL/6J mice were divided into 9 groups (n = 10/group; normal, Western diet, and 7 Western diet-strains [10 9 CFU/g, 8 weeks]). The strains used were L. bulgaricus, L. casei, L. helveticus, P. pentosaceus KID7, and three combinations (1: L. casei+L. helveticus, 2: L. casei+L. helveticus+P. pentosaceus KID7, and 3: L. casei+L. helveticus+L. bulgaricus ). Liver/Body weight ratio, serum and stool analysis, liver pathology, and metagenomics by 16S rRNA-sequencing were examined. In the liver/body ratio, L. bulgaricus (5.1 ± 0.5), L. helveticus (5.2 ± 0.4), P. pentosaceus KID7 (5.5 ± 0.5), and combination1 and 2 (4.2 ± 0.6 and 4.8 ± 0.7) showed significant reductions compared with Western (6.2 ± 0.6)(p < 0.001). In terms of cholesterol and steatosis/inflammation/NAFLD activity, all groups except for L. casei were associated with an improvement ( p < .05). The elevated level of tumor necrosis factor-α/interleukin-1β (pg/ml) in Western (65.8 ± 7.9/163.8 ± 12.2) was found to be significantly reduced in L. bulgaricus (24.2 ± 1.0/58.9 ± 15.3), L. casei (35.6 ± 2.1/62.9 ± 6.0), L. helveticus (43.4 ± 3.2/53.6 ± 7.5), and P. pentosaceus KID7 (22.9 ± 3.4/59.7 ± 12.2)(p < 0.01). Cytokines were improved in the combination groups. In metagenomics, each strains revealed a different composition and elevated Firmicutes / Bacteroidetes ratio in the western (47.1) was decreased in L. bulgaricus (14.5), L. helveticus (3.0), and P. pentosaceus KID7 (13.3). L. bulgaricus, L. casei, L. helveticus, and P. pentosaceus KID7 supplementation can improve NAFLD-progression by modulating gut-microbiome and inflammatory pathway.